Penentuan Komposisi Optimum Pembuatan Paving Block Berbahan Pasir Silika Proses Sand Blasting dengan Metode Taguchi - ndaru candra sukmana; Dedy Eko Prasetyono; ufafa anggraini (CHEMICA: Jurnal Teknik Kimia, 2017)
Sandblasting process by using silica sand will produce waste of silica sand at least 70%. Engineering Procurement and Construction (EPC) Industry produces a waste of untreated and unused sandblasting sand silica from sandblasting process. Silica sand waste sandblasting process is a dangerous waste. On the other hand development in Indonesia will increase. It takes a large amount of raw materials to meet development needs. One of the raw materials is paving block. Silica sand waste can be utilized as an alternative material for making paving block. In this research, the experiment design used is Taguchi method. The Taguchi method is used to determine the effect of silica sand waste and the optimum composition on the paving block to produce maximum compressive strength value. The results of this study indicate that silica sand waste hasnâ€™t an significant effect on the compressive strength of paving block and the optimum composition is 1.1 kg of cement, 2.5 kg of sand, and 2 kg of silica sand which produce a compressive strength of 21,56 MPa. The compressive strength is compliant with paving block SNI-03-0691-1996 on the classification of B quality that is with a minimum compressive strength of 17.0 MPa.Keywords: Â sandblasting wate, paving block, taguchi method